1976
DOI: 10.1111/j.1439-0418.1976.tb04204.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the dependence Microplitis rufiventris Kok. (Hym., Braconidae) parasitizing Spodoptera littoralis (Boisd.) on own food as well as on food of its host

Abstract: When S. littoralis parasitized larvae with M. rufiventris were fed on different plant leaf hosts, the bionomics of this parasitoid, in its different stages, were affected. Castor‐oil leaves were, then, most suitable food to the parasitized host larvae of S. littoralis, than other host plants. Adults of M. rufiventris were affected by the food plant of its host. Adults life of M. rufiventris prolonged, when reared on S. littoralis host larvae fed on castor oil longer than when other plants were used. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…It is interesting to note that cowpea provided an even safer host plant for the larvae in the four-choice test, and that maize was generally the plant leading to the lowest fitness proxies for the parasitoids, although it was the plant with the second-most attacked larvae in choice tests. Such impacts of host plants on the performance of parasitoids had been previously shown for this system: castor oil and sweet potato leaves were more edible and suitable for M. rufiventris developing in S. littoralis compared to cotton leaves (Altahtawy et al, 1976).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…It is interesting to note that cowpea provided an even safer host plant for the larvae in the four-choice test, and that maize was generally the plant leading to the lowest fitness proxies for the parasitoids, although it was the plant with the second-most attacked larvae in choice tests. Such impacts of host plants on the performance of parasitoids had been previously shown for this system: castor oil and sweet potato leaves were more edible and suitable for M. rufiventris developing in S. littoralis compared to cotton leaves (Altahtawy et al, 1976).…”
Section: Discussionsupporting
confidence: 67%
“…Our results confirmed that M. rufiventris is synovigenic, having some eggs at emergence but producing more during its adult life (Khafagi et al, 2011), although the egg loads at emergence in our study were higher than those in Khafagi et al's study. As in most parasitoids, M. rufiventris development time, egg load, longevity, and size were previously shown to be affected by the host quality, through host age or plant host (Altahtawy et al, 1976;Hegazi et al, 2007), so the observed impact of host plant on cocoon size, adult longevity, and female egg load was not surprising.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although studies on the effects of specific plant chemicals on parasitoid fitness are limited, it is generally concluded that plant defence chemicals mostly have a negative impact on natural enemy traits such as development time, survivorship and body size (Thurston & Fox 1972;Campbell & Duffey 1979, 1981Barbosa et al 1986;El-Heneidy et al 1988;Barbosa et al 1991;Thaler 1999Thaler , 2002Dicke 2006). These effects can strongly vary among plant species (Smith 1957;Altahtawy et al 1976;Bhatt & Singh 1989;Senrayan & Annadurai 1991;Werren et al 1992;Fox et al 1996;Kruse & Raffa 1997;Eben et al 2000;Harvey et al 2003;Zvereva & Rank 2003;Lu et al 2004) and even among cultivars of a same plant species (Kauffman & Flanders 1985;Orr & Boethel 1985;Hare & Luck 1991;Reed et al 1991;Rogers & Sullivan 1991;Riggin et al 1992;Stark et al 1992;Dosdall & Ulmer 2004;Kahuthia-Gathu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These effects can strongly vary among plant species (Smith 1957;Altahtawy et al 1976;Bhatt & Singh 1989;Senrayan & Annadurai 1991;Werren et al 1992;Fox et al 1996;Kruse & Raffa 1997;Eben et al 2000;Harvey et al 2003;Zvereva & Rank 2003;Lu et al 2004) and even among cultivars of a same plant species (Kauffman & Flanders 1985;Orr & Boethel 1985;Hare & Luck 1991;Reed et al 1991;Rogers & Sullivan 1991;Riggin et al 1992;Stark et al 1992;Dosdall & Ulmer 2004;KahuthiaGathu et al 2008).…”
Section: Introductionmentioning
confidence: 99%